Representação política e seus meandros: percepções da relação entre eleitos e eleitores - Silva, Felipe Nogueira Alves da (2016)
Analysis of political representation centered on the elements that make up the connective links between representatives and the represented. From the objective of understanding the political phenomenon of representation and ways of development investigated the relationship between elected and electors and its intricacies in order to know if the representation happens or if there is a link in a crisis, in which the responsiveness from one part to another does not occur or are not effective. Started with a theoretical approach to political representation, they are brought approaches and measurements of Political authors on the subject. And worked theories from the theoretical aspect, the representation as a political phenomenon is analyzed from the study of three phenomena that occur within it: the elections, the role of political parties and the action of the mass media. With the understanding of these three elements, their relationships and influence in political representation, sought to diagnose as the phenomenon develops and if it is experiencing a period of crisis or reset their forms of relationship. The next moment launches hand of empirical research and the use of results from interviews with former representatives belonging to the State Legislature and members of civil society organizations Capixaba, serving the results of example in order to demonstrate the theoretical explanations and guide the conclusion about the representation with respect to its development, the characterization of their relationship and their effectiveness. In conclusion we present the new ways that political representation goes to obey today, as a result of the modification of the forms of communication that expose other alternatives besides the mass media means such as the Internet, as well as the decline of the role of political parties in the relations of mediation between the candidate/politician and their constituents, both at election time as in office. The understanding that comes from the political representation phenomenon today is a framework of changes and adjustments, based on the new realities that arise in social and political relations that expose a link between representatives and represented that keeps. And despite the windings that are imposed from the capital strength and social inequality promoted by reality dominant and dominated strata, new ways of political representation point by endure connection and responsiveness between representatives and constituents, removing a sense of crisis.